Manajemen Kurikulum Pesantren Berbasis Panca Jiwa Pondok: Studi Kasus di Pondok Pesantren Darul Falah - Ana Mega Selviani; Eti Hadiati; Sovia Mas Ayu (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
This study examines pesantren curriculum management as a strategic instrument for internalizing Panca Jiwa Pondok sincerity, simplicity, independence, Islamic brotherhood, and responsible freedom among students at Pondok Pesantren Darul Falah through curriculum planning, organization, implementation, and evaluation. Using a qualitative case study design, data were collected through observation, in-depth interviews, and documentation involving the pesantren leader, teachers, administrators, and students. Data analysis followed Miles and Huberman’s interactive model of data reduction, data display, conclusion drawing, and verification, with credibility strengthened through triangulation, member checking, and an audit trail. The findings show that curriculum planning is participatory and integrates the national curriculum with a pesantren-based curriculum rooted in Panca Jiwa Pondok. Curriculum organization involves role distribution, scheduling, and the management of intracurricular, co-curricular, extracurricular, and dormitory-based activities, while implementation occurs through formal learning, kitab kuning studies, congregational worship, student organizations, teacher role modeling, and daily habituation. Evaluation is conducted continuously by assessing academic achievement, attitudes, discipline, responsibility, independence, simplicity, and social relationships. Fieldwork began in October 2025, with documented interviews and observations conducted on 30 October and 7 November 2025. The source materials identify three institutional interviewees the pesantren leader, curriculum staff/ustadz, and an ustadzah while student-related evidence was obtained through observation and institutional records. Overall, the study concludes that pesantren curriculum management functions not only as an administrative mechanism but also as a holistic value-management system, highlighting the need to strengthen value-based curriculum documentation and develop more systematic, measurable, and sustainable character evaluation instruments.